2020
DOI: 10.3390/ijms21239109
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Walled Carbon Nanotubes Can Promote Brassica napus L. and Arabidopsis thaliana L. Root Hair Development through Nitric Oxide and Ethylene Pathways

Abstract: Here, we report that multi-walled carbon nanotubes (MWCNTs) can promote plant root hair growth in the species analyzed in this study; however, low and excessive concentrations of MWCNTs had no significant effect or even an inhibiting influence. Further results show that MWCNTs can enter rapeseed root cells. Meanwhile, nitrate reductase (NR)-dependent nitric oxide (NO) and ethylene syntheses, as well as root hair formation, were significantly stimulated by MWCNTs. Transcription of root hair growth-related genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
(157 reference statements)
0
3
0
Order By: Relevance
“…29 Treating rapeseed seedlings with 100 mg/L multiwalled carbon nanotubes for 12 h induced a gradual increase in ET production in 3 days, which coincided with increased activities of enzymes involved in ET biosynthesis and regulation. 30 The absence of a wound response in these studies might have occurred because this reaction usually starts within minutes to hours after plant injury. Studies often concentrate on producing defensive compounds, such as secondary metabolites, which can take days to weeks and vary based on the wound's severity and plant species.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…29 Treating rapeseed seedlings with 100 mg/L multiwalled carbon nanotubes for 12 h induced a gradual increase in ET production in 3 days, which coincided with increased activities of enzymes involved in ET biosynthesis and regulation. 30 The absence of a wound response in these studies might have occurred because this reaction usually starts within minutes to hours after plant injury. Studies often concentrate on producing defensive compounds, such as secondary metabolites, which can take days to weeks and vary based on the wound's severity and plant species.…”
Section: Resultsmentioning
confidence: 92%
“…After 6-week-old A. thaliana leaves were infiltrated with SWNTs (50 mg/L) for 48 h, transcriptome analysis revealed that genes linked to immune responses and biotic and abiotic stress responses were notably upregulated . Treating rapeseed seedlings with 100 mg/L multiwalled carbon nanotubes for 12 h induced a gradual increase in ET production in 3 days, which coincided with increased activities of enzymes involved in ET biosynthesis and regulation . The absence of a wound response in these studies might have occurred because this reaction usually starts within minutes to hours after plant injury.…”
Section: Resultsmentioning
confidence: 99%
“…the results of another study revealed that the entrance of MWCNTs into rapeseed (Brassica napus) root cells leads to the synthesis of nitric oxide and ethylene, thus significantly stimulating plant root hair growth . [78] of traditional pesticides on human and environmental components.…”
Section: Pesticidesmentioning
confidence: 99%